GABA Production in Lactococcus lactis Is Enhanced by Arginine and Co-addition of Malate - Laroute, Valérie; Yasaro, Chonthicha; Narin, Waranya; Mazzoli, Roberto; Pessione, Enrica; Cocaign-Bousquet, Muriel; Loubière, Pascal (Frontiers in Microbiology, 2016)
Lactococcus lactis NCDO 2118 was previously selected for its ability to decarboxylate glutamate to γ-aminobutyric acid (GABA), an interesting nutritional supplement able to improve mood and relaxation. Amino acid decarboxylation is generally considered as among the biochemical systems allowing lactic acid bacteria to counteracting acidic stress and obtaining metabolic energy. These strategies also include arginine deiminase pathway and malolactic fermentation but little is known about their possible interactions of with GABA production. In the present study, the effects of glutamate, arginine, and malate (i.e., the substrates of these acid-resistance pathways) on L. lactis NCDO 2118 growth and GABA production performances were analyzed. Both malate and arginine supplementation resulted in an efficient reduction of acidity and improvement of bacterial biomass compared to glutamate supplementation. Glutamate decarboxylation was limited to narrow environmental conditions (pH < 5.1) and physiological state (stationary phase). However, some conditions were able to improve GABA production or activate glutamate decarboxylation system even outside of this compass. Arginine clearly stimulated glutamate decarboxylation: the highest GABA production (8.6 mM) was observed in cultures supplemented with both arginine and glutamate. The simultaneous addition of arginine, malate, and glutamate enabled earlier GABA production (i.e., during exponential growth) at relatively high pH (6.5). As far as we know, no previous study has reported GABA production in such conditions. Although further studies are needed to understand the molecular basis of these phenomena, these results represent important keys suitable of application in GABA production processes.